Irregular Migrants in Belgium and the Netherlands: Aspirations and Incorporation - van Meeteren, Masja (Amsterdam University Press, 2014)
In 'Irregular Migrants in Belgium and the Netherlands', Masja van Meeteren studies the different ways in which irregular migrants live in Belgium and the Netherlands. The book offers an empirically grounded theoretical critique of the dominant research practice that focuses on 'survival strategies', relies on comparisons of migrant communities and overemphasizes structural explanations. Instead, Irregular Migrants takes irregular migrants´ aspirations as a starting point of analysis. Based on this innovative research approach, key questions are answered regarding the lives of irregular migrants. How can we understand their patterns of economic and social incorporation, the transnational activities they engage in, and the significance of different forms of capital? Drawing on intensive participant observation, as well as more than two hundred in-depth interviews with irregular migrants and representatives of organizations that are involved with them, Irregular Migrants develops much-needed contextualized insights. As such, it sheds new light on previous research findings and various deadlocked scholarly debates on irregular migrants in Western societies.